Differential Immunoreactivity to Bovine Convalescent Serum Between Mycoplasma bovis Biofilms and Planktonic Cells Revealed by Comparative Immunoproteomic Analysis - Chen, Shengli; Hao, Huafang; Zhao, Ping; Ji, Wenheng; Li, Mingxia; Liu, Yongsheng; Chu, Yuefeng (Frontiers in Microbiology, 2018)
Mycoplasma bovis is a major bovine pathogen that causes considerable economic losses in the cattle industry worldwide. Moreover, M. bovis biofilm can persist in the environment and its host. To date, M. bovis biofilm antigens recognized by bovine convalescent sera and their comparison with planktonic cells have not yet been explored. This study utilized an immunoproteomic approach using two-dimensional electrophoresis, immunoblotting using convalescent bovine serum, and subsequent matrix-assisted laser desorption/ionization time-of-flight tandem mass spectrometry (MALDI-TOF/TOF MS) to identify the immunoreactive proteins expressed in biofilm- and planktonic-grown M. bovis strain 08M. Results showed that M. bovis biofilms and planktonic cells demonstrate differential immunoreactivity to bovine convalescent serum for the first time. A total of 10 and 8 immunoreactive proteins were identified for biofilms and planktonic cells, respectively. To our knowledge, a total of 12 out of 15 had not been reported as immunoreactive proteins in M. bovis, and six were specific to M. bovis biofilms. Three proteins, namely, endoglucanase, thiol peroxidase, and one putative membrane protein, that is, mycoplasma immunogenic lipase A, were identified in planktonic cells and biofilms. Most of the identified proteins were cytoplasmic proteins that were mainly involved in transport and metabolism. Moreover, ATP binding, oxidoreductase activity, and GTP binding were their most representative molecular functions. DnaK and Tuf appeared to be the most interactive immunoreactive agent among the identified proteins. Furthermore, six proteins had potential as serodiagnostic antigens. These data will be helpful to improve our current understanding on the host response to M. bovis biofilms and planktonic cells, which may facilitate the development of novel molecular candidates of improved diagnostics and vaccines to prevent M. bovis infections.